Optical Glass and Optical Elements

JP7631403B2Active Publication Date: 2025-02-18HOYA CORPORATION +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023065417
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-04-13
Publication Date
2025-02-18
Estimated Expiration
2043-04-13

Smart Images

  • Figure 0007631403000001
    Figure 0007631403000001
  • Figure 0007631403000002
    Figure 0007631403000002
  • Figure 0007631403000003
    Figure 0007631403000003
Patent Text Reader

Abstract

To provide an optical glass having a low glass transition temperature, low dispersibility and excellent thermal stability.SOLUTION: There are provided: an optical glass having a glass composition which comprises, as represented by cation percentage, an S6+ content of more than 0.0 cation% and 30.0 cation% or less, an Al3+ content of more than 0.0 cation% and 30.0 cation% or less, a P5+ content of 5.0 cation% or more and 50.0 cation% or less, a Li+ content of 0.0 cation% or more and 51.0 cation% or less, a Na+ content of 0.0 cation% or more and 44.0 cation% or less, a K+ content of 0.0 cation% or more and 45.0 cation% or less, in which the total content R+ of Li+, Na+, K+ and Cs+ is 5.0 cation% or more, when the total content of Be2+, Mg2+, Ca2+, Sr2+ and Ba2+ is defined as R2+, the cation% ratio (R2+ / (Al3++R2+)) of R2+ to the total content of Al3+ and R2+ is 0.56 or less; and an optical glass having a glass composition which comprises, as represented by anion percentage, an O2- content of 10.0 anion% or more and 95.0 anion% or less, an F- content of 10.0 anion% or more and 90.0 anion% or less in which the external transmittance at a wavelength of 500 nm to 1000 nm is 80% or more in terms of a thickness of 10.0 mm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical glass and an optical element. [Background technology]

[0002] For example, Patent Document 1 discloses an optical glass having a low glass transition temperature. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] WO2003 / 037813 Summary of the Invention [Problem to be solved by the invention]

[0004] Glasses with low glass transition temperatures can be molded at low temperatures, which is preferable because deterioration of the mold due to heating is reduced and because inexpensive molds with low heat resistance can be used.

[0005] In imaging optical systems and projection optical systems such as projectors, lenses with different dispersions are combined to form a cemented lens, which allows the optical system to be made compact while correcting chromatic aberration. Low dispersion is generally not easy to achieve with plastic lenses. Therefore, optical glass with low dispersion is useful as a material for optical elements that constitute imaging optical systems and projection optical systems such as projectors.

[0006] In view of the above, the present inventors have investigated optical glasses having a low glass transition temperature and low dispersion, and have found that further improvement in thermal stability is desired.

[0007] An object of one aspect of the present invention is to provide an optical glass that has a low glass transition temperature, low dispersion, and excellent thermal stability. [Means for solving the problem]

[0008] One aspect of the present invention is In the glass composition expressed in cation percentage, S 6+ The content is more than 0.0 cationic percent and 30.0 cationic percent or less, Al 3+ The content is more than 0.0 cationic percent and 30.0 cationic percent or less, P 5+ The content is 5.0 cationic percent or more and 50.0 cationic percent or less, Li + The content is 0.0 cationic percent or more and 51.0 cationic percent or less, Na + The content is 0.0 cationic percent or more and 44.0 cationic percent or less, K + The content is 0.0 cationic percent or more and 45.0 cationic percent or less, Li + , Na + , K + and Cs + The total content of R + is 5.0 cation% or more, Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ The total content of R 2+ As, Al 3+ and R 2+ R for the total content of 2+ The cation ratio (R 2+ / (Al 3+ +R 2+ )) is 0.56 or less, In the glass composition shown in anion %: O 2- The content is 10.0 anion% or more and 95.0 anion% or less, F - The content is 10.0 anion% or more and 90.0 anion% or less, and Optical glass having an external transmittance of 80% or more at a wavelength of 500 nm to 1000 nm when converted to a thickness of 10.0 mm; Regarding.

[0009] The optical glass has the above glass composition and thus can have a low glass transition temperature and low dispersion, and can also exhibit excellent thermal stability. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide an optical glass having a low glass transition temperature, low dispersion and excellent thermal stability, and also to provide an optical element made of such an optical glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Optical glass] In the present invention and this specification, the content and total content of cationic components are expressed in terms of cationic % unless otherwise specified, and the content and total content of anionic components are expressed in terms of anionic % unless otherwise specified. Here, "cation %" is a value calculated by "(number of cations of interest / total number of cations in glass components) x 100" and means the molar percentage of the amount of cations of interest relative to the total amount of cationic components. Furthermore, "anion %" is a value calculated by "(number of anions of interest / total number of anions in glass components) x 100" and means the molar percentage of the amount of the anion of interest relative to the total amount of the anion components. The molar ratio of the contents of cationic components to each other is equal to the ratio of the contents, expressed as cationic %, of the cationic components in question. The content of each component can be quantified by known methods, such as inductively coupled plasma atomic emission spectrometry (ICP-AES), inductively coupled plasma mass spectrometry (ICP-MS), ion chromatography, and the like. Regarding the cationic component, for example, Al 3+ , P 5+ However, the valence of the cationic component (e.g., Al 3+ The valence of is +3, P 5+The valence of is +5) is a value determined by convention, and is the same as expressing Al, P, etc. on an oxide basis as Al2O3, P2O5, etc. m O n (A represents a cation, O represents oxygen, and m and n are stoichiometric integers.) For a component represented as s+ Here, s=2n / m. Therefore, for example, when analyzing and quantifying the glass composition, it is not necessary to analyze the valence of the cationic components. The same applies to the anionic components, and it is not necessary to analyze the valence of the anionic components when analyzing and quantifying the glass composition. In the present invention and this specification, the content of a component being 0.0% or 0.00%, or not containing or not incorporating the component means that the component is substantially not contained, and the content of the component is equal to or less than the impurity level. The impurity level or less means, for example, less than 0.01%.

[0012] In the present invention and this specification, the term "thermal stability" refers to the resistance to crystal precipitation when a molten glass solidifies.

[0013] Hereinafter, the glass transition temperature may be abbreviated as Tg.

[0014] The optical glass (sometimes simply referred to as "glass") will be described in more detail below.

[0015] <Glass composition> The glass composition of the above optical glass expressed in cation % will be described below.

[0016] S 6+From the viewpoints of lowering the Tg of the glass, maintaining the refractive index and low dispersion, and improving the thermal stability, the content is more than 0% and is preferably 0.5% or more, and more preferably in the following order: 1.0% or more, 1.2% or more, 1.3% or more, 1.4% or more, 1.5% or more, 1.6% or more, 1.7% or more, 1.8% or more, 1.9% or more, 2.0% or more, 2.1% or more, 2.2% or more, 2.3% or more, 2.4% or more, 2.5% or more, 2.6% or more, 2.7% or more, 2.8% or more, 2.9% or more, and 3.0% or more. Also, S 6+ From the viewpoints of maintaining the refractive index, maintaining the thermal stability, and suppressing an increase in the liquidus temperature, the content is 30.0% or less, preferably 29.0% or less, and more preferably 28.0% or less, 27.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, and 14.0% or less, in that order.

[0017] Al 3+ From the viewpoint of maintaining low dispersion while increasing the refractive index, and from the viewpoint of improving the thermal stability and maintaining the chemical durability of the glass, the content is more than 0.0% and is preferably 1.0% or more, and more preferably 2.0% or more, 3.0% or more, 4.0% or more, 5.0% or more, 6.0% or more, 7.0% or more, 8.0% or more, 9.0% or more, 10.0% or more, and 11.0% or more in that order. In addition, Al 3+ From the viewpoint of suppressing an increase in Tg, the content is 30.0% or less, preferably 29.0% or less, and more preferably 28.0% or less, 27.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, and 18.0% or less, in that order.

[0018] P 5+From the viewpoint of maintaining low dispersion and improving the thermal stability of the glass, the content is 5.0% or more, preferably 7.0% or more, and more preferably 9.0% or more, 11.0% or more, 13.0% or more, 14.0% or more, 15.0% or more, 16.0% or more, and 17.0% or more in that order. Also, P 5+ From the viewpoints of maintaining the refractive index, improving the thermal stability of the glass, and suppressing a decrease in chemical durability, the content is 50.0% or less, preferably 48.0% or less, and more preferably 46.0% or less, 44.0% or less, 42.0% or less, 40.0% or less, 38.0% or less, 37.0% or less, 36.0% or less, 35.0% or less, 34.0% or less, 33.0% or less, and 32.0% or less in that order.

[0019] Li + From the viewpoint of maintaining low dispersion while increasing the refractive index, and from the viewpoints of lowering the Tg of the glass, improving the meltability of the glass, and lowering the specific gravity, the content is 0.0% or more, preferably 1.0% or more, and more preferably 2.0% or more, 4.0% or more, 5.5% or more, 7.0% or more, 8.5% or more, 10.0% or more, 12.0% or more, 13.5% or more, 15.0% or more, 16.5% or more, 17.0% or more, 18.5% or more, and 20.0% or more in that order. Also, Li + From the viewpoint of improving the thermal stability of the glass and suppressing a decrease in chemical durability, the content is 51.0% or less, preferably 48.0% or less, and more preferably 45.0% or less, 43.0% or less, 41.0% or less, 40.0% or less, 39.0% or less, 38.0% or less, 37.0% or less, 36.0% or less, 35.0% or less, 34.0% or less, 33.0% or less, 32.0% or less, and 31.0% or less in that order.

[0020] Na + From the viewpoints of maintaining the refractive index, maintaining low dispersion, lowering the Tg of the glass, improving the meltability and lowering the specific gravity of the glass, the content is 0.0% or more, preferably 1.0% or more, and more preferably 2.0% or more, 3.0% or more, 4.0% or more, 5.0% or more, 6.0% or more, 7.0% or more, 8.0% or more, and 9.0% or more in that order. Also, Na+ From the viewpoint of improving the thermal stability of the glass and suppressing a decrease in chemical durability, the content is 44.0% or less, preferably 42.0% or less, and more preferably 40.0% or less, 38.0% or less, 36.0% or less, 34.0% or less, 32.0% or less, 30.0% or less, 28.0% or less, 26.0% or less, 24.0% or less, 22.0% or less, 20.0% or less, and 19.0% or less, in that order.

[0021] K + From the viewpoints of maintaining the refractive index, maintaining low dispersion, lowering the Tg of the glass, improving the meltability and lowering the specific gravity of the glass, the content is 0.0% or more, preferably 1.0% or more, and more preferably 2.0% or more, 3.0% or more, 4.0% or more, 5.0% or more, and 6.0% or more in that order. Also, K + From the viewpoints of improving the thermal stability of the glass, suppressing a decrease in chemical durability, and lowering the specific gravity, the content is 45.0% or less, and more preferably in the order of 43.0% or less, 40.0% or less, 38.0% or less, 36.0% or less, 34.0% or less, 32.0% or less, 30.0% or less, 28.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, and 15.0% or less.

[0022] Li + , Na + , K + and Cs + The total content of R + From the viewpoints of maintaining low dispersibility, lowering the Tg of the glass, lowering the specific gravity, and lowering the liquidus temperature, is 5.0% or more, preferably 10.0% or more, and more preferably 15.0% or more, 20.0% or more, 23.0% or more, 25.0% or more, 28.0% or more, 30.0% or more, 33.0% or more, 35.0% or more, 37.0% or more, 40.0% or more, and 42.0% or more in that order. Also, Li + , Na + , K + and Cs + The total content of R +From the viewpoints of maintaining low dispersion, maintaining the thermal stability of the glass, and suppressing a decrease in chemical durability, it is preferably 65.0% or less, and more preferably 64.0% or less, 63.0% or less, 62.0% or less, 61.0% or less, 60.0% or less, and 59.0% or less in that order.

[0023] Cs + The content can be 0.0%, can be 0.0% or more, or can be more than 0.0%. + From the viewpoint of lowering the Tg of the glass and improving the meltability of the glass, the content can be 0.0% or more, and is preferably 0.1% or more, and more preferably 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, and 0.6% or more, in that order. Also, Cs + From the viewpoint of improving the thermal stability of the glass and suppressing a decrease in chemical durability, the content is preferably 10.0% or less, and more preferably 8.0% or less, 6.0% or less, 4.0% or less, 2.0% or less, 1.5% or less, and 1.0% or less in that order.

[0024] Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ The total content of R 2+ In the above optical glass, Al 3+ and R 2+ R for the total content of 2+ The cation ratio (R 2+ / (Al 3+ +R 2+ )) is, from the viewpoint of suppressing an increase in Tg and maintaining the thermal stability of the glass, 0.56 or less, preferably 0.55 or less, and more preferably 0.54 or less, 0.53 or less, 0.52 or less, 0.51 or less, 0.50 or less, 0.49 or less, 0.48 or less, 0.47 or less, 0.46 or less, 0.45 or less, 0.44 or less, 0.43 or less, 0.42 or less, 0.41 or less, 0.40 or less, 0.39 or less, 0.38 or less, and 0.37 or less in that order. In addition, the cation ratio (R 2+ / (Al 3+ +R 2+)) can be 0.00 or more or more than 0.00, and from the viewpoint of lowering the Tg of the glass and improving the meltability of the glass, it is preferably 0.01 or more, more preferably 0.02 or more, and further preferably 0.03 or more.

[0025] Be 2+ The content may be 0.0%, 0.0% or more, or more than 0.0%. From the viewpoints of maintaining the refractive index, maintaining low dispersion, suppressing an increase in Tg, and maintaining the thermal stability of the glass, Be is 2+ The content is preferably 15.0% or less, more preferably 10.0% or less, and further more preferably 5.0% or less, 2.5% or less, 1.5% or less, 1.0% or less, and 0.5% or less, in that order. Mg 2+ The content may be 0.0%, 0.0% or more, or more than 0.0%. From the viewpoints of maintaining the refractive index, maintaining low dispersion, suppressing an increase in Tg, and maintaining the thermal stability of the glass, Mg 2+ The content is preferably 15.0% or less, more preferably 14.0% or less, and further more preferably 13.0% or less, 12.0% or less, 11.0% or less, and 10.0% or less in that order. Ca 2+ The content may be 0.0%, 0.0% or more, or more than 0.0%. From the viewpoints of maintaining the refractive index, maintaining low dispersion, suppressing an increase in Tg, and maintaining the thermal stability of the glass, Ca 2+ The content is preferably 15.0% or less, more preferably 14.0% or less, and further preferably 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, and 5.0% or less, in that order. Sr 2+ The content may be 0.0%, 0.0% or more, or more than 0.0%. From the viewpoints of maintaining the refractive index, maintaining low dispersion, suppressing an increase in Tg, and maintaining the thermal stability of the glass, Sr 2+ The content is preferably 10.0% or less, more preferably 9.0% or less, and further more preferably 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, and 4.0% or less in that order. Ba2+ The content may be 0.0%, 0.0% or more, or more than 0.0%. From the viewpoints of maintaining the refractive index, maintaining low dispersion, improving the meltability of the glass, suppressing an increase in Tg, and maintaining the thermal stability of the glass, Ba is preferably used. 2+ The content is preferably 10.0% or less, more preferably 9.0% or less, and further more preferably 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, and 2.0% or less. Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ The total content of R 2+ The total content R can be 0.0%, 0.0% or more, or more than 0.0%. From the viewpoints of maintaining the refractive index, maintaining low dispersion, suppressing an increase in Tg, and maintaining the thermal stability of the glass, 2+ is preferably 20.0% or less, more preferably 19.0% or less, and further preferably 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, and 10.0% or less in that order.

[0026] Zinc 2+ The content can be 0.0%, 0.0% or more or greater than 0.0%. Zn 2+ Although Zn functions to improve thermal stability while maintaining the refractive index, its excessive content tends to increase dispersion. 2+ The content is preferably 20.0% or less, more preferably 19.0% or less, and further preferably 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, and 10.0% or less, in that order.

[0027] Zr 4+ The content can be 0.0%, 0.0% or more or greater than 0.0%. 4+is a component that increases the refractive index, but if contained in excess, dispersion tends to increase and Tg tends to rise. 4+ The content is preferably 10.0% or less, more preferably 9.0% or less, and further more preferably 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, and 2.0% or less.

[0028] Al 3+ and P 5+ P relative to the total content of 5+ Cation content ratio (P 5+ / (Al 3+ +P 5+ )) is preferably 0.30 or more, more preferably 0.35 or more, and further preferably 0.40 or more, 0.45 or more, and further preferably 0.50 or more, in this order, from the viewpoints of maintaining low dispersibility, further improving the thermal stability of the glass, further lowering the Tg of the glass, and improving the meltability of the glass. In addition, the cation ratio (P 5+ / (Al 3+ +P 5+ )) is preferably 0.85 or less, more preferably 0.83 or less, and further more preferably 0.81 or less, 0.80 or less, 0.79 or less, 0.78 or less, 0.77 or less, 0.76 or less, 0.75 or less, 0.74 or less, 0.73 or less, 0.72 or less, and 0.71 or less, in that order.

[0029] R + and R 2+ Li for the sum of + Cation ratio of content (Li + / (R + +R 2+ )) is preferably 0.00 or more, more preferably 0.05 or more, and further preferably 0.10 or more, 0.13 or more, 0.15 or more, 0.17 or more, 0.20 or more, 0.23 or more, 0.25 or more, 0.27 or more, 0.30 or more, 0.33 or more, 0.35 or more, 0.37 or more, and 0.40 or more, in this order. In addition, the cation ratio (Li + / (R + +R 2+ )) is preferably 1.00 or less, more preferably 0.95 or less, and further more preferably 0.92 or less, 0.90 or less, 0.88 or less, 0.85 or less, 0.83 or less, 0.80 or less, 0.78 or less, 0.75 or less, 0.72 or less, 0.70 or less, 0.67 or less, 0.65 or less, 0.63 or less, and 0.60 or less, in that order.

[0030] Al 3+ and P 5+ R for the total content of + The cation ratio (R + / (Al 3+ +P 5+ )) is preferably 0.93 or more, more preferably 0.95 or more, and further preferably 0.97 or more, 0.99 or more, 1.01 or more, 1.03 or more, 1.05 or more, 1.07 or more, 1.09 or more, 1.11 or more, 1.13 or more, 1.14 or more, 1.15 or more, or 1.16 or more, from the viewpoints of maintaining low dispersibility, further lowering the Tg of the glass, improving the meltability of the glass, and lowering the specific gravity. In addition, the cation ratio (R + / (Al 3+ +P 5+ )) is preferably 2.00 or less, more preferably 1.98 or less, and further more preferably 1.96 or less, 1.94 or less, 1.92 or less, 1.90 or less, 1.88 or less, 1.87 or less, 1.86 or less, and 1.85 or less, in that order, from the viewpoints of maintaining the refractive index, maintaining low dispersion, and maintaining the thermal stability of the glass.

[0031] Al 3+ and P 5+ Li relative to the total content of + and K. + The cation ratio of the total content of (Li + +K + ) / (Al 3+ +P 5+)) is preferably 0.56 or more, more preferably 0.58 or more, and further preferably 0.60 or more, 0.62 or more, 0.64 or more, 0.66 or more, 0.68 or more, 0.70 or more, 0.72 or more, 0.74 or more, 0.76 or more, 0.78 or more, and 0.80 or more, in this order, from the viewpoints of maintaining low dispersibility, further lowering the Tg of the glass, improving the meltability of the glass, and lowering the specific gravity. In addition, the cation ratio ((Li + +K + ) / (Al 3+ +P 5+ )) is preferably 1.40 or less, more preferably 1.38 or less, and further preferably 1.36 or less, 1.34 or less, 1.32 or less, 1.30 or less, 1.28 or less, 1.27 or less, 1.26 or less, and 1.25 or less, in that order, from the viewpoints of maintaining the refractive index, maintaining low dispersion, and maintaining thermal stability.

[0032] Li + and K. + Li relative to the total content of + and Na + The cation ratio of the total content of (Li + +Na + ) / (Li + +K + )) is preferably 0.50 or more, more preferably 0.55 or more, and further more preferably 0.60 or more, 0.65 or more, 0.70 or more, 0.75 or more, 0.80 or more, 0.85 or more, 0.86 or more, 0.87 or more, 0.88 or more, 0.89 or more, and 0.90 or more, in this order, from the viewpoint of further lowering the Tg of the glass and improving the meltability of the glass. Cation ratio ((Li + +Na + ) / (Li + +K +)) is preferably 1.59 or less, more preferably 1.57 or less, and further more preferably 1.55 or less, 1.53 or less, 1.51 or less, 1.49 or less, 1.47 or less, 1.45 or less, 1.43 or less, 1.41 or less, 1.39 or less, 1.37 or less, 1.35 or less, 1.33 or less, 1.31 or less, 1.29 or less, 1.28 or less, 1.27 or less, 1.26 or less, 1.25 or less, and 1.24 or less, in that order.

[0033] Pb, As, Cd, Tl, Be and Se are each toxic, and therefore it is preferable not to contain these elements, i.e., not to introduce these elements into the glass as glass components. U, Th and Ra are all radioactive elements, and therefore it is preferable not to contain these elements, i.e., not to introduce these elements into the glass as glass components. V, Cr, Mn, Fe, Co, Ni, Cu, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, Tm and Ce are not preferred elements to be contained in glass for optical elements because they can increase the coloring of the glass or become a source of fluorescence. Therefore, it is preferable not to contain these elements, i.e., not to introduce these elements into the glass as glass components.

[0034] Sb and Sn are optional elements that function as fining agents. The Sb content of the optical glass can be, for example, 0.40% or less, 0.20% or less, 0.10% or less, 0.05% or less, 0.02% or less, or 0.01% or less, expressed as a mass fraction (%) of Sb2O3 when the mass of the glass is taken as 100. On the other hand, the Sb content can be 0.00% or more, or can be 0.00%, expressed as a mass fraction (%) of Sb2O3 when the mass of the glass is taken as 100. The Sn content of the optical glass can be, for example, 0.40% or less, 0.20% or less, 0.10% or less, 0.05% or less, 0.02% or less, or 0.01% or less, expressed as a mass fraction (%) of SnO2 when the mass of the glass is taken as 100. On the other hand, the Sn content can be 0.00% or more, or can be 0.00%, expressed as a mass fraction (%) of SnO2 when the mass of the glass is taken as 100.

[0035] Now that the cationic component has been described, the anionic component will be described.

[0036] The optical glass contains at least O as an anion component. 2- and F - Includes.

[0037] O 2- From the viewpoint of increasing the refractive index and improving the thermal stability of the glass, the content is 10.0% or more, preferably 15.0% or more, and more preferably in the following order: 17.5% or more, 20.0% or more, 22.5% or more, 25.0% or more, 27.5% or more, 30.0% or more, 32.5% or more, 35.0% or more, 37.5% or more, 40.0% or more, 42.5% or more, 45.0% or more, 48.0% or more, 49.0% or more, 50.0% or more, 51.0% or more, 52.0% or more, 53.0% or more, 54.0% or more, 55.0% or more, 56.0% or more, 57.0% or more, 58.0% or more, and 59.0% or more. Also, O 2- From the viewpoints of maintaining low dispersion and suppressing an increase in the Tg of the glass, the content is 95.0% or less, preferably 88.5% or less, and more preferably 86.0% or less, 83.5% or less, 82.0% or less, 81.0% or less, 80.0% or less, 79.0% or less, 78.0% or less, and 77.0% or less, in that order.

[0038] F -From the viewpoint of maintaining the low dispersion of the glass and achieving a low Tg, the content is 10.0% or more, preferably 11.00% or more, and more preferably 12.00% or more, 13.00% or more, 14.00% or more, 15.00% or more, 16.00% or more, 17.00% or more, 18.00% or more, 19.00% or more, 20.00% or more, 21.00% or more, 22.00% or more, and 23.00% or more in that order. Also, F - From the viewpoint of improving the thermal stability of the glass and suppressing volatilization of the glass during melting, the content is 90.0% or less, preferably 85.0% or less, and more preferably in the order of 80.0% or less, 75.0% or less, 70.0% or less, 65.0% or less, 63.0% or less, 60.0% or less, 57.0% or less, 55.0% or less, 54.0% or less, 52.0% or less, 50.0% or less, 49.0% or less, 48.0% or less, 47.0% or less, 46.0% or less, 45.0% or less, 44.0% or less, and 43.0% or less.

[0039] O 2- and F - Examples of anion components other than Cl include - , Br - and I - Examples include: Cl - The content can be, for example, 0.0%, 0.0% or more, more than 0.0%, 0.10% or more, or 0.20% or more, and can be, for example, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, or 0.50% or less. Br - The content can be, for example, 0.0%, 0.0% or more, more than 0.0%, 0.10% or more, or 0.20% or more, and can be, for example, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, or 0.5% or less. I - The content can be, for example, 0.0%, 0.0% or more, more than 0.0%, 0.10% or more, or 0.20% or more, and can be, for example, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, or 0.5% or less.

[0040] <Glass properties> (Abbe number νd) The optical glass can exhibit low dispersion by having the above glass composition. The Abbe number νd, which is an index of dispersion, is expressed as νd=(nd-1) / (nF-nC) using the refractive indices nd, nF, and nC at the d-line, F-line, and C-line. From the viewpoint of usefulness as a material for optical elements, the Abbe number νd of the optical glass is preferably 70.00 or more, more preferably 70.50 or more, and further preferably 71.00 or more, 71.50 or more, 72.00 or more, 72.50 or more, and 73.00 or more in that order. The Abbe number νd of the optical glass can be, for example, 82.00 or less.

[0041] (Refractive index nd) From the viewpoint of usefulness as a material for optical elements, the refractive index nd of the optical glass can be, for example, 1.420 or more, 1.425 or more, 1.430 or more, 1.435 or more, 1.440 or more, 1.445 or more, 1.446 or more, 1.447 or more, 1.448 or more, 1.449 or more, or 1.450 or more, and can be, for example, 1.510 or less, 1.505 or less, 1.500 or less, 1.4950 or less, 1.490 or less, 1.489 or less, 1.488 or less, 1.487 or less, 1.486 or less, 1.485 or less, 1.484 or less, 1.483 or less, or 1.482 or less. In the present invention and this specification, "refractive index" means "refractive index nd". Refraction nd is the refractive index at a wavelength of 587.56 nm.

[0042] (glass transition temperature Tg) The optical glass can have a low glass transition temperature by having the above glass composition. The glass transition temperature Tg of the optical glass is preferably 350°C or less, more preferably 340°C or less, and further preferably 330°C or less, 320°C or less, 310°C or less, 300°C or less, 290°C or less, 280°C or less, 270°C or less, and 260°C or less in this order. The glass transition temperature Tg of the optical glass can be, for example, 150°C or more, 160°C or more, 170°C or more, 180°C or more, 190°C or more, or 200°C or more. The glass transition temperature Tg is determined by the method described below.

[0043] (specific gravity) The specific gravity of the optical glass is preferably low from the viewpoint of reducing the weight of the optical element.The specific gravity of the optical glass can be, for example, 3.10 or less, 3.05 or less, 3.00 or less, 2.95 or less, 2.90 or less, or 2.85 or less.The specific gravity of the optical glass can be, for example, 2.55 or more, but the lower limit is not particularly limited because the lower the specific gravity, the more preferable it is.

[0044] (Transmittance characteristics) The optical glass has an external transmittance of 80% or more at wavelengths of 500 nm to 1000 nm, calculated as a thickness of 10.0 mm. "An external transmittance of 80% or more at wavelengths of 500 nm to 1000 nm, calculated as a thickness of 10.0 mm" means that the external transmittance is 80% or more at a thickness of 10.0 mm over the entire wavelength range of 500 nm to 1000 nm. The optical glass can have an external transmittance of 80% or more and 100% or less at a thickness of 10.0 mm, calculated as a thickness of 10.0 mm, at wavelengths of 500 nm to 1000 nm. Optical glass having such transmittance characteristics is useful as a material for optical elements. For example, when Cu is used as a cationic component, 2+ By using glass that does not contain the above, the above transmittance characteristics can be achieved.

[0045] The transmittance characteristics of the above glass are determined by the following method. The glass sample is processed to have parallel and optically polished flat surfaces, and the external transmittance is measured at wavelengths of 500 to 1000 nm. The external transmittance includes the reflection loss of light rays on the sample surface. In addition, if the glass to be measured does not have a thickness that can be converted, the thickness of the glass is taken as d, and the transmittance at each wavelength λ is converted using the following formula A, and the transmittance characteristics are obtained by conversion.

[0046] Formula A: T(λ)=(1-R(λ)) 2 ×exp(log e ((T0(λ) / 100) / (1-R(λ)) 2 )×d / d0)×100

[0047] In formula A, T(λ): converted transmittance at wavelength λ (%), T0(λ): measured transmittance at wavelength λ (%), d: converted thickness (mm), d0: glass thickness (mm), R(λ)=((n(λ)-1) / (n(λ)+1)) 2 The reflectance at wavelength λ is expressed as n(λ): refractive index at wavelength λ. The refractive index n(λ) at wavelength λ is measured at each wavelength in accordance with the Japanese Industrial Standards (JIS) JIS B 7071-1 "Method of measuring refractive index of optical glass - Part 1: Minimum deviation method."

[0048] <Method of manufacturing optical glass> The optical glass can be obtained by weighing, compounding, and thoroughly mixing raw materials such as phosphates, fluorides, oxides, carbonates, sulfates, nitrates, and hydroxides so as to obtain the desired glass composition, heating and melting the mixture in a melting vessel, degassing, and stirring to produce a homogeneous, bubble-free molten glass, and then molding the glass. Specifically, the glass can be produced by using a known melting method.

[0049] [Glass material for press molding, optical element blanks, and their manufacturing methods] Another aspect of the present invention is a glass material for press molding comprising the optical glass; an optical element blank made of the optical glass; Regarding.

[0050] According to another aspect of the present invention, a method for producing a glass material for press molding, comprising a step of molding the optical glass into a glass material for press molding; a method for producing an optical element blank, comprising a step of press-molding the glass material for optical glass press molding using a press mold to produce an optical element blank; A method for producing an optical element blank, comprising the step of forming the optical glass into an optical element blank; will also be provided.

[0051] An optical element blank is an optical element base material that approximates the shape of a target optical element and has polishing margins (surface layers to be removed by polishing) and, if necessary, grinding margins (surface layers to be removed by grinding) added to the shape of the optical element. The optical element is finished by grinding and polishing the surface of the optical element blank. In one embodiment, the optical element blank can be produced by a method (called a direct press method) in which a molten glass obtained by melting an appropriate amount of the above glass is press-molded. In another embodiment, the optical element blank can also be produced by solidifying a molten glass obtained by melting an appropriate amount of the above glass.

[0052] In another embodiment, a glass material for press molding is prepared, and the prepared glass material for press molding is press molded to produce an optical element blank.

[0053] The press molding of the glass material for press molding can be carried out by a known method in which the glass material for press molding in a heated and softened state is pressed in a press mold. Both heating and press molding can be carried out in the atmosphere. By annealing after press molding to reduce distortion inside the glass, a homogeneous optical element blank can be obtained.

[0054] Glass materials for press molding include not only those called glass gobs for press molding, which are used for press molding as they are to produce optical element blanks, but also those that are mechanically processed such as by cutting, grinding, polishing, etc., and are used for press molding via glass gobs for press molding. Cutting methods include a method in which a groove is formed in the portion of the surface of the glass plate to be cut by a method called scribing, and local pressure is applied to the grooved portion from the back side of the surface on which the groove is formed, thereby breaking the glass plate at the grooved portion, and a method in which the glass plate is cut by a cutting blade. Grinding and polishing methods include barrel polishing, etc.

[0055] The glass material for press molding can be produced, for example, by casting molten glass into a mold to form a glass plate, and cutting this glass plate into a plurality of glass pieces. Alternatively, a suitable amount of molten glass can be molded to produce a glass gob for press molding. An optical element blank can also be produced by reheating, softening, and press-molding the glass gob for press molding. The method of producing an optical element blank by reheating, softening, and press-molding glass is called a reheat press method, as opposed to a direct press method.

[0056] [Optical elements and their manufacturing methods] Another aspect of the present invention is An optical element made of the above optical glass Regarding. The optical element is produced using the optical glass. In the optical element, the glass surface may be coated with one or more layers of coating, such as a multilayer film including an anti-reflection film.

[0057] According to another aspect of the present invention, A method for producing an optical element, comprising the step of producing an optical element by grinding and / or polishing the optical element blank described above; will also be provided.

[0058] In the manufacturing method of the optical element, the mechanical processing such as grinding and polishing can be performed by applying a known method, and the surface of the optical element after processing can be sufficiently cleaned and dried to obtain an optical element with high internal quality and surface quality. In this way, an optical element made of the optical glass can be obtained. Examples of optical elements include various lenses such as spherical lenses, aspherical lenses, and microlenses, and prisms.

[0059] In addition, the optical element made of the optical glass is also suitable as a lens constituting a cemented optical element. Examples of cemented optical elements include a cemented lens formed by cementing lenses together, and a lens and a prism. For example, a cemented optical element can be produced by precisely processing (for example, spherical polishing) the cemented surfaces of two optical elements to be cemented so that the shapes are inverted, applying an ultraviolet-curing adhesive used for bonding cemented lenses, bonding them together, and then irradiating ultraviolet rays through the lens to cure the adhesive. A plurality of optical elements to be cemented can be produced using a plurality of types of glass having different Abbe numbers νd, and cementing them together to produce an element suitable for correcting chromatic aberration. EXAMPLES

[0060] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.

[0061] [Example 1] <Sample No. 1 to 88> In order to obtain the glass composition shown in the table below, the corresponding phosphates, fluorides, nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. were used as raw materials for introducing each component, and the raw materials were weighed and thoroughly mixed to obtain blended raw materials. The mixed raw materials were placed in a platinum crucible and heated and melted for 90 minutes in a furnace set at 700 to 1100° C. The molten glass was stirred to homogenize it, then poured into a preheated mold and allowed to cool to near the glass transition temperature. It was then immediately placed in an annealing furnace and held at about the glass transition temperature for about 30 minutes, after which it was slowly cooled at a rate of -30° C. / hour for 4 hours, and then allowed to cool to room temperature in the furnace to obtain the optical glasses of Samples 1 to 88 shown in the table below.

[0062] [Comparative example A, comparative example B] In order to obtain the glass composition shown in the table below, the corresponding phosphates, fluorides, nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. were used as raw materials for introducing each component, and the raw materials were weighed and thoroughly mixed to obtain blended raw materials. The mixed raw materials were placed in a platinum crucible, and heated in a furnace set at 700 to 1100°C for 90 minutes. After stirring and homogenizing the molten glass, the molten glass was poured into a preheated mold and allowed to cool to near the glass transition temperature, and then immediately placed in an annealing furnace. The glass was held at about the glass transition temperature for about 30 minutes, and then slowly cooled at a slow cooling rate of -30°C / hour for 4 hours, and then allowed to cool to room temperature in the furnace, thereby obtaining the optical glasses of Comparative Examples A and B shown in the following table. The optical glasses of Comparative Examples A and B were obtained. Comparative Example A corresponds to Example 33 of WO2003 / 037813 (Patent Document 1), and Comparative Example B corresponds to Example 35 of WO2003 / 037813 (Patent Document 1).

[0063] <Physical property evaluation> The physical properties of each optical glass shown in the following table were measured by the following methods.

[0064] (1) Refractive index nd Abbe number νd The refractive index nd and Abbe number vd of each optical glass were measured by the refractive index measurement method of the Japan Optical Glass Industry Association standard. For Comparative Example A, the refractive index nd and Abbe number vd could not be measured because the glass was devitrified.

[0065] (2) Glass transition temperature Tg The glass was thoroughly crushed in a mortar and used as a sample. A platinum cell was used as a sample container, and the glass transition temperature Tg was measured at a heating rate of 10°C / min using a differential scanning calorimeter (DSC3300SA) manufactured by NETZSCH JAPAN.

[0066] (3) Specific gravity Specific gravity was measured by Archimedes' method.

[0067] (4) Transmittance characteristics A test piece was cut out from the obtained glass, and both sides were mirror-polished to have parallel, optically polished flat surfaces to a thickness of 10.0 mm. The external transmittance at wavelengths of 500 to 1000 nm was then measured using a spectrophotometer. It was confirmed that for all of Samples Nos. 1 to 88, Comparative Example A, and Comparative Example B, the external transmittance in the wavelength range of 500 nm to 1000 nm was 80% or more and 100% or less at a thickness of 10.0 mm.

[0068] <Evaluation of thermal stability> For Samples No. 1 to 88, Comparative Example A, and Comparative Example B, the corresponding phosphates, fluorides, nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. were used as raw materials for introducing each component so as to obtain the glass composition shown in the table below, and the raw materials were weighed and thoroughly mixed to obtain blended raw materials. The mixed raw materials were placed in a platinum crucible and melted for 90 minutes in a furnace set at 700 to 1100° C. The molten glass was stirred to homogenize it, and then cast into a mold to be shaped, and slowly cooled to obtain a block-shaped glass sample. The obtained glass samples were observed for crystals in the glass using an optical microscope. The magnification of the optical microscope was 40 to 100 times. When no crystals were observed in the glass block, it was rated as A, and when it was rated as 1 cm 3 B: 1 to 15 crystals per 1 cm 3 C if 16 to 40 crystals were found per cm 3If more than 40 crystals were found per glass, it was rated D. For A, B, and C, the order of thermal stability is C → B → A, with A being the most thermally stable. If the results are A, B, or C, the internal quality is within the acceptable range in terms of the number of crystals contained in the glass during manufacturing. Glass rated D is poor in thermal stability and has poor internal quality during manufacturing. As shown in the table below, it was confirmed that the glasses of Samples No. 1 to 88 were excellent in thermal stability (evaluation result A, B, or C).

[0069] [Table 1-1]

[0070] [Table 1-2]

[0071] [Table 1-3]

[0072] [Table 1-4]

[0073] [Table 1-5]

[0074] [Table 1-6]

[0075] [Table 1-7]

[0076] [Table 1-8]

[0077]

Table 1-9

[0078]

Table 2-1

[0079]

Table 2-2

[0080]

Table 2-3

[0081]

Table 2-4

[0082]

Table 2-5

[0083]

Table 2-6

[0084]

Table 2-7

[0085]

Table 2-8

[0086]

Table 2-9

[0087] Example 2 A glass gob for press molding was prepared using the various glasses obtained in Example 1. The glass gob was heated and softened in the atmosphere, and press molded in a press mold to prepare a lens blank (optical element blank). The prepared lens blank was removed from the press mold, annealed, and machined, including polishing, to prepare a spherical lens made of the various glasses prepared in Example 1.

[0088] Example 3 A desired amount of the molten glass produced in Example 1 was press molded in a press mold to produce a lens blank (optical element blank). The produced lens blank was removed from the press mold, annealed, and subjected to mechanical processing including polishing to produce a spherical lens made of the various glasses produced in Example 1.

[0089] Example 4 The molten glass produced in Example 1 was solidified to produce a glass lump (optical element blank), which was then annealed and machined, including polishing, to produce spherical lenses made of the various glasses produced in Example 1.

[0090] Finally, the above-mentioned aspects will be summarized.

[0091] [1] In the glass composition expressed in cation percentage, S 6+ The content is more than 0.0 cations and 30.0 cations or less. Al 3+ The content is more than 0.0 cationic percent and 30.0 cationic percent or less, P 5+ The content is 5.0 cationic percent or more and 50.0 cationic percent or less, Li + The content is 0.0 cationic percent or more and 51.0 cationic percent or less, Na + The content is 0.0 cationic percent or more and 44.0 cationic percent or less, K + The content is 0.0 cationic percent or more and 45.0 cationic percent or less, Li + , Na+ , K + and Cs + The total content of R + is 5.0 cation% or more, Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ The total content of R 2+ As, Al 3+ and R 2+ R for the total content of 2+ The cation ratio (R 2+ / (Al 3+ +R 2+ )) is 0.56 or less, In the glass composition shown in anion %: O 2- The content is 10.0 anion% or more and 95.0 anion% or less, F - The content is 10.0 anion% or more and 90.0 anion% or less, and Optical glass with an external transmittance of 80% or more at a wavelength of 500nm to 1000nm when converted to a thickness of 10.0mm. [2] Al 3+ and P 5+ P relative to the total content of 5+ Cation content ratio (P 5+ / (Al 3+ +P 5+ )) is 0.30 or more and 0.85 or less. [3] R + and R 2+ Li for the sum of + Cation ratio of content (Li + / (R + +R 2+ )) is 0.00 or more and 1.00 or less. [4] Al 3+ and P 5+ R for the total content of + The cation ratio (R + / (Al 3+ +P 5+)) is 0.93 or more. [5] Al 3+ and P 5+ Li relative to the total content of + and K. + The cation ratio of the total content of (Li + +K + ) / (Al 3+ +P 5+ )) is 0.56 or more. [6] Li + and K. + Li relative to the total content of + and Na + The cation ratio of the total content of (Li + +Na + ) / (Li + +K + )) is 0.50 or more and 1.59 or less. [7] The optical glass according to any one of [1] to [6], which has a glass transition temperature Tg of 150° C. or higher and 350° C. or lower. [8] The optical glass according to any one of [1] to [7], having an Abbe number vd of 70.00 or more and 82.00 or less. [9] Al 3+ and P 5+ P relative to the total content of 5+ Cation content ratio (P 5+ / (Al 3+ +P 5+ ) is 0.30 or more and 0.85 or less, R + and R 2+ Li for the sum of + Cation ratio of content (Li + / (R + +R 2+ )) is greater than or equal to 0.00 and less than or equal to 1.00, Al 3+ and P 5+ R for the total content of + The cation ratio (R + / (Al 3+ +P 5+ ) is 0.93 or more, Al 3+ and P 5+ Li relative to the total content of + and K. + The cation ratio of the total content of (Li + +K + ) / (Al 3+ +P 5+ ) is 0.56 or more, Li + and K. + Li relative to the total content of + and Na + The cation ratio of the total content of (Li + +Na + ) / (Li + +K + ) is 0.50 or more and 1.59 or less, The glass transition temperature Tg is 150°C or higher and 350°C or lower, and The optical glass according to [1], having an Abbe number vd of 70.00 or more and 82.00 or less.

[10] An optical element comprising the optical glass according to any one of [1] to [9].

[0092] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by subjecting the above-mentioned exemplary glass compositions to compositional adjustments as described in the specification, an optical glass according to one aspect of the present invention can be obtained. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.

Claims

1. In the glass composition expressed in cation percentage, S 6+ A content of more than 0.0% cationic percent and not more than 30.0% cationic percent, A 3+ A content of more than 0.0 cationic percent and not more than 30.0 cationic percent, P 5+ The content is 5.0 cationic percent or more and 50.0 cationic percent or less, Li + The content is 0.0 cationic percent or more and 51.0 cationic percent or less, Na + The content is 0.0 cationic percent or more and 44.0 cationic percent or less, K + The content is 0.0 cationic percent or more and 45.0 cationic percent or less, Li + , Na + , K + and Cs + The total content R + is 5.0 cation% or more, B 2+ , Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ The total content of R 2+ As Al 3+ and R 2+ R for the total content of 2+ The cation ratio (R 2+ / (Al 3+ +R 2+ ) is 0.56 or less, a cation ratio (Li + / (R + +R 2+ )) of the Li + content to the total of R + and R 2+ is 0.30 or more; the cation ratio of R + to the total content of Al 3+ and P 5+ (R + / (Al 3+ +P 5+ )) is 0.93 or more; a cation ratio ((Li++Na++) / (Li++K++)) of the total content of Li+ and Na+ to the total content of Li+ and K+ is 0.50 or more and 1.59 or less; In the glass composition expressed as anion percentage, O 2- The content is 10.0 anion % or more and 95.0 anion % or less, F - The content is 10.0 anion% or more and 90.0 anion% or less, Abbe number νd is 70.00 or more and 82.00 or less, A glass transition temperature Tg of 310° C. or less, and, An optical glass having an external transmittance of 80% or more at wavelengths of 500 nm to 1000 nm when converted into a thickness of 10.0 mm.

2. A 3+ and P 5+ P relative to the total content of 5+ The cationic ratio of the content (P 5+ / (Al 3+ +P 5+ 2. The optical glass according to claim 1, wherein the refractive index is 0.30 or greater and 0.85 or less.

3. R + and R 2+ Li for the sum of + The cation ratio of the content (Li + / (R + +R 2+ 2. The optical glass according to claim 1, wherein R 1 is 0.30 or greater and 1.00 or less.

4. A 3+ and P 5+ Li relative to the total content of + and K. + The cation ratio of the total content of (Li + +K + ) / (Al 3+ +P 5+ 2. The optical glass according to claim 1 , wherein the refractive index is 0.56 or greater.

5. 2. The optical glass according to claim 1, which has a glass transition temperature Tg of 150° C. or higher and 310° C. or lower.

6. A 3+ and P 5+ P relative to the total content of 5+ The cationic ratio of the content (P 5+ / (Al 3+ +P 5+ ) is 0.30 or more and 0.85 or less, R + and R 2+ Li for the sum of + The cation ratio of the content (Li + / (R + +R 2+ ) is 0.30 or more and 1.00 or less, A 3+ and P 5+ Li relative to the total content of + and K. + The cation ratio of the total content of (Li + +K + ) / (Al 3+ +P 5+ ) is 0.56 or more, and 2. The optical glass according to claim 1, which has a glass transition temperature Tg of 150° C. or higher and 310° C. or lower.

7. An optical element comprising the optical glass according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Glass

    JP2014125395A

  • Glass for near-infrared absorption filter

    JP2016060671A

  • Optical glass suitable for mold forming

    WO2003037813A1